Value estimating of the sedimentation rate at the shipwreck sites (MV Boelongan Nederland) the Mandeh Bay Region-Pesisir Selatan Regency. Issue 1 (January 2022) - Hermon, D; Gusman, M; Putra, A; Dewata, I
Abstract: Sufficiently high sediment deposit at the shipwreck diving site (MV Boelongan Nederland) the Mandeh bay region - Pesisir Selatan Regency due to infrastructure development has resulted in significant changes in the physical environment and may affect the existence of the shipwreck diving site. The analysis method regarding the sedimentation rate is carried out based on data from sediment traps that have been installed at the location of the shipwreck diving site, river flow, and river estuary. Based on the sedimentation rate measurement from the sediment trap, there is a close relationship between the sediment supply of the Mandeh river flow and the Nyalo river flow that affects the sedimentation rate at the shipwreck diving site. Where it was found the sedimentation rate in the shipwreck diving site was 15, 33 g.m- 2 day- 1 . With the condition of the waters of Mandeh bay region being semi-closed from open water, it is suspected that the sediment contributed from these rivers is mostly trapped and settled in these water areas.